การคำนวณเบี้ยประกันชีวิตแบบชีวิตร่วมพหุลดลง - จิราพัชร พันธ์พัฒนกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purpose of this research is to calculate the multiple decrement joint life insurance premiums for dependence future life time. Data used in this research are the number of population and the number of death by sex, age, marital status and cause of death of the year 2006-2009 from the Ministry of Interior and the Ministry of Public Health respectively. Mortality rate and joint survival function of population are calculated by using Frank’s copula function. Then mortality rate and joint survival function of population are used instead of mortality rate and joint survival function of insured to calculate the multiple decrement joint life insurance premium. The results show that the multiple decrement joint life insurance premiums for dependence future life time are difference from the multiple decrement joint life insurance premiums for independence future life time. The multiple decrement joint life insurance premiums for dependence future life time depend on degree of dependence future life time of joint insured.